Self-Propelled Micro/Nanomotors (MNMs) and Their Applications - Ye, Heng (Curtin University, 2018)
The majority of the micro/nanomotors use the precious noble metal platinum for propulsion. However, platinum suffers from high-cost, scarcity, and possibility of deactivation in various media. In this thesis, we explored the MnO2 based materials for the fabrication of the high-performance and low-cost micro/nanomotors. These newly developed MnO2 based micromotors show great potential for replacing Pt and will greatly improves the applications of micro/nanomotors for biomedical science and environmental remediations areas.